Perkembangan Pertunjukan Salawat Dulang di Minangkabau - Syafniati, Syafniati; Firdaus, Firdaus; Amran, Amran (LP2M ISBI Bandung, 2019)
ABSTRACTThe purpose of this study is to examine the factors that cause the development and changes in Salawat Dulang which initially had a function as a means of preaching. Salawat Dulang is one of traditional art that uses vocal and dulang as instruments. The poem delivered at salawat dulang contains Islamic teachings including remembrance of Allah SWT and praise to the prophet Muhammad SAW. Based on the current situation there has been developments and changes in Salawat Dulang which has resulted in changes of function to entertainment performances. This study used qualitative method as well as anthropology, sociology, and aesthetic approaches.Data collection techniques are carried out in several ways including observation, interviews, and documentation. The results found on the development and changes in Salawat Dulang are caused by both internal, and external factors by not changing existing values. changes occurred in the presentation of vocals adobted from modern and popular songs, so as to better adapt to the tastes of the supporting communityKeywords : Salawat Dulang, Performing Art and Developmen ABSTRAKTujuan Penelitian adalah untuk membahas perkembangan dan perubahan pertunjukan salawat dulang yang pada awalnya berfungsi sebagai sarana dakwah. Salawat dulang merupakan kesenian bernuasa Islam yang disajikan dalam bentuk vokal dan diiringi oleh pukulan dulang sebagai musik pengiring. Syair yang disampaikan berisikan ajaran Islam berupa zikir kepada Allah SWT dan pujian kepada nabi Muhammad SAW. Seiring perkembangan zaman salawat dulang mengalami pergeseran menjadi seni pertunjukan. Penelitian ini menggunakan metode deskriptif analisis dengan pendekatan antropologi, sosiologi, dan estetika. Pengumpulan data dilakukan melalui observasi, wawancara, dan dokumentasi. Hasil penelitian menunjukkan bahwa perkembangan dan perubahan salawat dulang dipengaruhi oleh faktor internal dan eksternal dengan tidak merubah nilai-nilai tradisi yang ada. Perubahan terjadi pada penyajian vokal yang mengadopsi lagu-lagu modern dan populer, sehingga lebih menyesuaikan dengan selera masyarakat pendukungnya. Kata kunci: salawat dulang, seni pertunjukan dan perkembangan